2017
DOI: 10.1093/eurpub/ckx210
|View full text |Cite
|
Sign up to set email alerts
|

Primary care for refugees and newly arrived migrants in Europe: a qualitative study on health needs, barriers and wishes

Abstract: Health of refugees on the move in Europe is jeopardized by their bad living circumstances and barriers in access to healthcare. To address their needs, healthcare workers have to be trained in providing integrated, compassionate and cultural competent healthcare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
85
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 15 publications
7
85
0
10
Order By: Relevance
“…On the one hand culture-related communication differences were identified as hampering for mental health diagnoses, on the other hand there is a lack of mental health care options available targeted especially to refugees [15,16]. The results of this research are consistent to earlier studies [18–20].…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…On the one hand culture-related communication differences were identified as hampering for mental health diagnoses, on the other hand there is a lack of mental health care options available targeted especially to refugees [15,16]. The results of this research are consistent to earlier studies [18–20].…”
Section: Introductionsupporting
confidence: 86%
“…Research has shown that PHC professionals and refugees or other migrants face equally great challenges when it comes to PHC encounters during the flight, upon and after arrival in the destination countries [15,16,18–20]. In response to these challenges, an online course/CME course for PHC professionals was developed, offering comprehensive knowledge on the issues of refugees’ and other migrants’ health to participants from different countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study detected respiratory tract infections in 41% of 33,331 patients who accessed care points of entry into Greece and Serbia [16,17,36,37]. Moreover, pregnancy-related issues are often mentioned [25,28,38]. In some cases, young mothers are too stressed to breastfeed their newborns.…”
Section: Health Problems Facing Refugeesmentioning
confidence: 99%
“…Although some refugees refused to receive any care because they wanted to continue their journey as soon as possible, the majority reported that they received inadequate information about the rules in the holding centers, as well as on the organization and location of health services [38]. …”
Section: The Refugee Crisis Challenges the Greek Healthcare Systemmentioning
confidence: 99%